Preparation and application of composite polyamide membrane

By using the combination of PE/PET composite short fiber support layer and polyamide layer, the problem of insufficient mechanical strength and chemical stability of PSF or PES films in harsh environments is solved, and reverse osmosis with high water flux and high interception is achieved Membrane, suitable for water treatment.

CN119215698APending Publication Date: 2024-12-31JIANGNAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411377394.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing TFC membranes supported by PSF or PES are insufficient in harsh environments, resulting in poor resistance to organic solvents, limiting their application range.

Method used

Using PE/PET composite short fibers as the support layer, wet forming and hot pressing drying to form a support body, and the sodium dodecyl sulfate and trimethylol chloride solution are treated successively on its surface to form a polyamide layer to improve the film Mechanical strength and solvent resistance.

Benefits of technology

It significantly improves the water flux and retention rate of the composite polyamide film, enhances its stability to organic solvents, and is suitable for the application of reverse osmosis membranes in water treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215698A_ABST
    Figure CN119215698A_ABST
Patent Text Reader

Abstract

The invention discloses preparation and application of a composite polyamide membrane, and belongs to the field of membrane separation. The composite polyamide membrane comprises a supporting layer and a polyamide layer, the supporting layer is a PE / PET composite short fiber membrane, and the polyamide layer contains a reaction product of m-phenylenediamine and trimesoyl chloride. The preparation method of the composite polyamide membrane comprises the following steps: dispersing PE / PET composite short fibers, polyoxyethylene and cationic polyacrylamide in deionized water, then forming on a former, and then carrying out hot-pressing drying to obtain a support body; the preparation method comprises the following steps: preparing a supporting body, sequentially treating the supporting body by using a m-phenylenediamine solution containing lauryl sodium sulfate and a trimesoyl chloride solution containing trimellitic anhydride acyl chloride to form a polyamide layer on the surface, and finally carrying out heat treatment to obtain the composite polyamide membrane. The composite polyamide membrane has excellent water flux, relatively high rejection rate and relatively good chemical stability, and the contact stability of the polyamide membrane and an organic solvent is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of membrane separation, and in particular relates to the preparation and application of a composite polyamide membrane. Background Art

[0002] With the development of society and the increase of world population, fresh water has always been the most scarce resource for human beings, and membrane separation technology is an important way to produce fresh water. In the past few decades, polyamide (PA) thin film composite (TFC) membranes have been widely used as commercial reverse osmosis (RO) membranes for seawater desalination due to their high permeability selectivity. Metaphenylenediamine (MPD) and trimethylol chloride (TMC) are dissolved in two immiscible solvents and a PA selective layer is formed on a porous support by interfacial polymerization (IP) to prepare PA-TFC membranes. For TFC membranes, the support layer determines its chemical and mechanical stability, while the PA selective layer mainly controls its separation performance. Although each membrane component can be selected independently, the structure and chemical properties of the support have a crucial influence on the structure and separation performance of the formed PA layer, thereby restricting the selection of support materials. For example, it is known that a support with moderate hydrophobicity is conducive to the manufacture of a highly permeable selectivity PA layer, which is consistent with the fact that commercial reverse osmosis membranes mainly use polysulfone (PSF) or polyethersulfone (PES) as support materials.

[0003] However, PSF- or PES-supported TFC membranes have technical limitations when applied in harsh environments due to their relatively low mechanical strength and poor chemical stability (or resistance to organic solvents).

[0004] At present, there are reports that some other polymer materials are used to increase mechanical strength and chemical stability, thereby changing its use restrictions in harsh environments. However, the above methods cannot completely eliminate the intolerance of PSF commercial substrate membranes to organic solvents. Summary of the invention

[0005] The purpose of the present invention is to overcome the technical limitations of existing commercial PSF or PES supported TFC membranes when used in harsh environments due to their relatively low mechanical strength and poor chemical stability (or resistance to organic solvents).

[0006] In order to achieve the above objectives,

[0007] A first aspect of the present invention provides a composite polyamide membrane, which comprises a support layer and a polyamide layer, wherein the support layer comprises a PE / PET composite short fiber membrane substrate, and the polyamide layer comprises a reaction product of m-phenylenediamine and trimesoyl chloride.

[0008] A second aspect of the present invention provides a method for preparing a composite polyamide membrane, the method comprising the following steps:

[0009] S1, dispersing PE / PET composite short fibers, polyethylene oxide, and cationic polyacrylamide in deionized water, stirring and mixing to obtain a uniform mixed solution, and forming the mixed solution on a former to obtain an intermediate;

[0010] S2, hot pressing and drying the intermediate to obtain a support having a certain strength and pore size distribution;

[0011] S3, sequentially treating the support with a m-phenylenediamine solution containing sodium dodecyl sulfate and a trimesoyl chloride solution containing trimellitic anhydride chloride to form a polyamide layer on the surface of the support to obtain a composite polyamide membrane.

[0012] The third aspect of the present invention provides a method for simultaneously improving the water flux, rejection rate and solvent resistance of a reverse osmosis membrane, the method comprising the following steps:

[0013] S1, dispersing PE / PET composite short fibers, polyethylene oxide, and cationic polyacrylamide in deionized water, stirring and mixing to obtain a uniform mixed solution, and forming the mixed solution on a former to obtain an intermediate;

[0014] S2, hot pressing and drying the intermediate to obtain a support having a certain strength and pore size distribution;

[0015] S3, sequentially treating the support with a m-phenylenediamine solution containing sodium dodecyl sulfate and a trimesoyl chloride solution containing trimellitic anhydride chloride to form a polyamide layer on the surface of the support, and finally heat treating to obtain a composite polyamide membrane.

[0016] Furthermore, in step S1, the dispersion process includes: firstly dissolving the polyoxyethylene and cationic polyacrylamide in deionized water to form a polyoxyethylene solution system and a cationic polyacrylamide solution system respectively, and then adding the dispersion of PE / PET composite staple fibers and stirring to obtain a uniform mixed solution.

[0017] Furthermore, in the dispersion process, the polyoxyethylene is a dispersant and the cationic polyacrylamide is a reinforcing agent.

[0018] Furthermore, the mass ratio of the total mass of the polyoxyethylene and cationic polyacrylamide to deionized water is 1:100-200. Preferably, the concentration of the polyoxyethylene solution system is 0.5-0.6wt%. The concentration of the cationic polyacrylamide solution system is 0.5-0.6wt%.

[0019] Furthermore, the concentration of the dispersion of the PE / PET composite short fibers is 4.5-10 mg / mL.

[0020] Furthermore, the mass ratio of PE / PET composite staple fibers, polyethylene oxide, and cationic polyacrylamide is (100-500):1:(0.5-1.5).

[0021] Furthermore, in step S1, the stirring conditions at least include: a temperature of 20-30°C, a stirring rate of 500-700 rpm, and a time of 10-20 min.

[0022] Furthermore, the process of dissolving polyoxyethylene and cationic polyacrylamide in deionized water is to mix polyoxyethylene, cationic polyacrylamide and deionized water and then perform ultrasonic treatment.

[0023] Furthermore, the conditions of the ultrasonic treatment at least include: ultrasonic power of 250-300W and time of 8-12h.

[0024] Furthermore, in step S2, the intermediate support body is dried using an oil press and a vacuum drying oven.

[0025] Furthermore, the conditions for hot pressing and drying include at least: a pressure of 5 MPa, a hot pressing temperature of 100° C., and a hot pressing time of 5-10 min.

[0026] Furthermore, in step S3, m-phenylenediamine and trimesoyl chloride are contacted with the support to react, thereby obtaining a composite membrane having a polyamide layer; during the reaction, sodium dodecyl sulfate and trimellitic anhydride chloride are added to promote the formation of the polyamide membrane.

[0027] Furthermore, in step S3, the support is treated with a m-phenylenediamine solution containing sodium dodecyl sulfate and a trimesoyl chloride solution containing trimellitic anhydride chloride in sequence to form a polyamide layer on the surface of the support, constituting a cycle. The cycle is repeated 0-2 times, and finally heat-treated to obtain a composite polyamide membrane.

[0028] Furthermore, in step S3, the solvent used in the m-phenylenediamine solution is deionized water.

[0029] Furthermore, in step S3, the solvent used in the trimesoyl chloride solution is n-hexane.

[0030] Furthermore, in step S3, the concentration of m-phenylenediamine in the m-phenylenediamine solution is 3-4wt%; and the concentration of sodium dodecyl sulfate is 0.05-0.1wt%.

[0031] Furthermore, in step S3, the concentration of trimesoyl chloride in the trimesoyl chloride solution is 0.15-0.2 wt %; the concentration of trimellitic anhydride chloride is 0.08-0.1 wt %.

[0032] Further, in step S3, S3 specifically includes the following process: immersing the support in the m-phenylenediamine solution containing sodium dodecyl sulfate for 15-25 minutes, and then pouring an organic phase solution of n-hexane containing trimesoyl chloride (TMC) and trimellitic anhydride chloride (TAC) onto the surface of the modified base film to react for 50-70 seconds.

[0033] Preferably, the heat treatment conditions at least include: a temperature of 65-75° C. and a time of 10-20 min.

[0034] A fourth aspect of the present invention provides the use of the composite polyamide membrane and / or the composite polyamide membrane prepared by the above method in the field of reverse osmosis.

[0035] Through the above technical solution, the beneficial effects of the present invention are:

[0036] The composite polyamide membrane provided by the present invention uses a support body obtained by wet-forming PE / PET composite short fibers as a support layer for a polyamide layer, so that the strength of the composite polyamide membrane is improved, the water flux is increased, and the organic solvent resistance of the composite polyamide membrane is greatly improved; sodium dodecyl sulfate and trimellitic anhydride chloride are added to promote the synthesis of the polyamide membrane, and multi-layer cyclic polymerization improves the salt rejection rate of the polyamide membrane. The composite polyamide membrane can be used as a reverse osmosis membrane in water treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The following are characterization spectra of the support and composite membrane products obtained in Example 1. In which: Figure (a) is a support obtained by wet forming of PE / PET composite short fibers, Figure (b) is a polyamide membrane obtained by multilayer cyclic polymerization on the surface of the support, Figures (c) and (d) are partial magnified images of the support and the polyamide membrane at an electron microscope magnification of 20 μm, respectively. In Figure (c), dispersants and reinforcing agents attached to the fiber surface can be found, and Figure (d) shows that a polyamide membrane is synthesized on the surface of the support. DETAILED DESCRIPTION

[0038] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0039] A first aspect of the present invention provides a composite polyamide membrane, which comprises a support layer and a polyamide layer, wherein the support layer contains PE / PET composite short fibers formed by a wet process, and the polyamide layer contains a reaction product of m-phenylenediamine and trimesoyl chloride.

[0040] The inventor of the present invention unexpectedly discovered during the research process that by adding sodium dodecyl sulfate and trimellitic anhydride chloride to the existing polyamide membrane interfacial polymerization, the structural parameter S value of the composite polyamide membrane is significantly reduced, the water permeation transmission resistance is small, and the water flux is high, which greatly improves the stability of the composite polyamide membrane to organic solvents and improves its water flux and salt rejection rate; the composite polyamide membrane can be used as a reverse osmosis membrane in water treatment.

[0041] The inventors have found that under this preferred embodiment, multi-layer circulation of the composite polyamide membrane can effectively increase the water flux and salt rejection rate, and improve the reverse osmosis treatment efficiency.

[0042] The inventors found that the interfacial polymerization reaction forms a polyamide layer on the surface of the support, constituting a cycle, and the cycle is repeated 0-2 times. Under this preferred embodiment, it is beneficial to further reduce the structural parameters and transmission resistance of the composite polyamide membrane.

[0043] A second aspect of the present invention provides a method for preparing a composite polyamide membrane, the method comprising the following steps:

[0044] S1, dispersing PE / PET composite short fibers, polyethylene oxide, and cationic polyacrylamide in deionized water, stirring and mixing to obtain a uniform mixed solution, and forming the mixed solution on a former to obtain an intermediate;

[0045] S2, hot pressing and drying the intermediate by means of an oil press and a vacuum drying oven to obtain a support having a certain strength and pore size distribution;

[0046] S3, sequentially treating the support with a m-phenylenediamine solution containing sodium dodecyl sulfate and a trimesoyl chloride solution containing trimellitic anhydride chloride to form a polyamide layer on the surface of the support to obtain a composite polyamide membrane.

[0047] In the present invention, the polyoxyethylene and cationic polyacrylamide raw materials are commercially available polyoxyethylene and cationic polyacrylamide.

[0048] According to the present invention, preferably, in step S1, the weight ratio of the total mass of the polyoxyethylene and cationic polyacrylamide to the deionized water is 1:100-200. The inventors found that under this preferred embodiment, the dispersion efficiency of polyoxyethylene and cationic polyacrylamide is improved.

[0049] According to the present invention, preferably, in step S1, the weight of the PE / PE composite staple fiber is 0.94-1.88 g.

[0050] According to the present invention, preferably, in step S1, the mixing conditions at least include: a temperature of 20-30°C, specifically 20°C, 22°C, 24°C, 26°C, 28°C, 30°C, or any value between the above two values; a stirring rate of 500-700rpm, specifically 500rpm, 550rpm, 600rpm, 650rpm, 700rpm, or any value between the above two values; a time of 10-20min, specifically 10min, 12min, 14min, 16min, 18min, 20min, or any value between the above two values. The inventors found that under this preferred embodiment, it is beneficial to uniformly disperse polyoxyethylene and cationic polyacrylamide.

[0051] According to the present invention, preferably, in step S1, the mass ratio of PE / PET composite staple fibers, polyethylene oxide, and cationic polyacrylamide is (100-500):1:(0.5-1.5).

[0052] According to the present invention, preferably, the dispersion process includes: first dissolving the polyoxyethylene and cationic polyacrylamide in deionized water to form a polyoxyethylene solution system and a cationic polyacrylamide solution system respectively, and then adding a dispersion of PE / PET composite staple fibers and stirring to obtain a uniform mixed solution.

[0053] According to the present invention, further, the polyoxyethylene is a dispersant, and the concentration of the polyoxyethylene solution system is 0.5-0.6 wt %.

[0054] According to the present invention, further, the cationic polyacrylamide is a reinforcing agent, and the concentration of the cationic polyacrylamide solution system is 0.5-0.6wt%.

[0055] According to the present invention, further, ultrasonic treatment is used in the process of dissolving polyoxyethylene and cationic polyacrylamide in deionized water to accelerate the dispersion rate of polyoxyethylene and cationic polyacrylamide and improve the dispersion effect.

[0056] According to the present invention, preferably, the conditions of the ultrasonic treatment at least include: the ultrasonic power is 250-300W, specifically 250W, 260W, 270W, 280W, 290W, 300W, or any value between the above two values; the time is 8-12h, specifically 8h, 9h, 10h, 11h, 12h, or any value between the above two values. The inventors found that under this preferred embodiment, it is beneficial to improve the dispersion efficiency of polyoxyethylene and cationic polyacrylamide.

[0057] In the present invention, in step S2, the intermediate is hot-pressed and dried by an oil press and a vacuum drying oven to obtain a support having a certain strength and pore size distribution.

[0058] In the present invention, in step S2, the drying is carried out in a vacuum drying manner. Preferably, the drying conditions at least include: a pressure of 5 MPa, a hot pressing temperature of 100° C., and a hot pressing time of 5-10 min.

[0059] According to the present invention, in step S3, the solvent used for the m-phenylenediamine solution can be a conventional solvent in which m-phenylenediamine is soluble, and the trimesoyl chloride solution can be a conventional solvent in which trimesoyl chloride is soluble.

[0060] Preferably, in step S3, the solvent used in the m-phenylenediamine solution is deionized water, and the solvent used in the trimesoyl chloride solution is n-hexane.

[0061] According to the present invention, preferably, the concentration of m-phenylenediamine is 3-4 wt %, and the concentration of sodium dodecyl sulfate is 0.05-0.1 wt %.

[0062] The concentration of trimesoyl chloride is 0.15-0.2 wt %, and the concentration of trimellitic anhydride chloride is 0.08-0.1 wt %.

[0063] According to the present invention, preferably, the specific process of step S3 includes: immersing the support in a m-phenylenediamine solution containing sodium dodecyl sulfate for 15-25 minutes, and carefully removing excess solution with an air gun; then pouring an organic phase solution of n-hexane containing trimesoyl chloride (TMC) and trimellitic anhydride chloride (TAC) onto the surface of the modified base film to react for 50-70 seconds, and immediately removing excess solution, so that m-phenylenediamine (MPD) and trimesoyl chloride (TMC) are interfacially polymerized on the surface of the modified base film to form a polyamide active layer.

[0064] In the present invention, the support body can be fixed in a frame, exposing the surface of the support body, and then immersed in a m-phenylenediamine solution containing sodium dodecyl sulfate for 15-25 minutes, and the excess solution is carefully removed with an air gun; then an organic phase solution containing monomers of trimesoyl chloride and trimellitic anhydride chloride is poured onto the surface of the modified base film and reacted for 50-70 seconds, and the excess solution is immediately removed to form a polyamide layer on the surface of the support body, constituting a cycle, and the cycle is repeated 0-2 times to obtain the final product polyamide film.

[0065] According to the present invention, preferably, the method further comprises subjecting the composite polyamide membrane to a heat treatment to obtain a composite polyamide membrane having a polyamide layer after a curing treatment.

[0066] In the present invention, the heat treatment process can be carried out in an oven. Preferably, the heat treatment conditions at least include: a temperature of 55-75°C, specifically 55°C, 60°C, 65°C, 70°C, 75°C, or any value between the above two values; a time of 10-20 minutes, specifically 10 minutes, 12 minutes, 14 minutes, 16 minutes, 18 minutes, 20 minutes, or any value between the above two values.

[0067] According to a particularly preferred embodiment of the present invention, the method for preparing the composite polyamide membrane comprises the following steps:

[0068] S1. After polyoxyethylene and cationic polyacrylamide are mixed with deionized water at a weight ratio of 1:100-200, they are first subjected to ultrasonic treatment at an ultrasonic power of 250-300 W for 8-12 hours to obtain polyoxyethylene and cationic polyacrylamide dispersions, the polyoxyethylene and cationic polyacrylamide dispersions are mixed with PPE / PET composite short fiber dispersions at a temperature of 20-30° C. and a stirring rate of 500-700 rpm for 10-20 minutes to obtain a mixed solution, and an intermediate is obtained by wet forming technology;

[0069] S2, hot pressing and drying the intermediate by means of an oil press and a vacuum drying oven to obtain a support having a certain strength and pore size distribution;

[0070] S3. Immerse the support in an aqueous solution of m-phenylenediamine containing sodium dodecyl sulfate for reaction for 15-25 minutes, blow dry to remove excess aqueous solution, and then pour the mixed monomer trimesoyl chloride (TMC) and trimellitic anhydride chloride (TAC) in n-hexane organic phase solution onto the surface of the modified base film to react for 50-70 seconds, then immediately remove excess solution to form a polyamide layer on the surface of the support, constituting a cycle, and repeat the cycle 0-2 times to obtain a PA membrane, which is heat treated at a temperature of 65-75°C for 10-20 minutes to obtain a composite polyamide membrane with a polyamide layer.

[0071] The composite polyamide membrane provided by the present invention has high mechanical strength, low water permeation transmission resistance, and high water flux, which greatly improves the organic solvent resistance of the composite polyamide membrane. The third aspect of the present invention provides the application of the composite polyamide membrane and / or the composite polyamide membrane prepared by the above method in reverse osmosis technology.

[0072] In the present invention, the reverse osmosis technology can be applied to water treatment or other liquid treatments, and has high osmosis efficiency.

[0073] The present invention will be described in detail below through examples.

[0074] In the following examples, polyoxyethylene was purchased from Jiangsu Aoshen New Materials Co., Ltd., cationic polyacrylamide was purchased from Jiangsu Fumiao Technology Co., Ltd., polyethylene / polyethylene terephthalate (PE / PET) composite staple fibers were purchased from Shandong Jinkeli Special Fiber Co., Ltd., and unless otherwise specified, the remaining raw materials or reagents were conventional commercially available products.

[0075] In the following examples, room temperature refers to 25±5°C.

[0076] Example 1

[0077] S1. Dissolve 500 mg of polyoxyethylene and 500 mg of cationic polyacrylamide in 100 mL of deionized water respectively, and use a probe ultrasonicator to ultrasonicate at a power of 270 W for 10 h to obtain polyoxyethylene and cationic polyacrylamide solutions; disperse 1.88 g of dry weight of PE / PET composite short fibers in 200 mL of deionized water, add 2 mL of polyoxyethylene and 2 mL of cationic polyacrylamide solution, use a constant temperature magnetic stirrer to mix at room temperature and a stirring rate of 600 rpm for 10 min to obtain a mixed solution, and add the mixed solution to a former to obtain an intermediate by wet forming;

[0078] S2, hot pressing the intermediate for 5 min through an oil press (pressure 5 MPa) and a vacuum drying oven (temperature 100° C.) to obtain a support having a certain strength and pore size distribution;

[0079] S3, fix the support in the frame, soak it in an aqueous solution containing 0.05wt% sodium dodecyl sulfate and 3wt% m-phenylenediamine for 15 minutes, blow off the excess aqueous solution with an air gun, and then pour a n-hexane solution containing 0.15wt% trimesoyl chloride and 0.08wt% trimellitic anhydride chloride onto the surface of the modified base film, and immediately remove the excess solution after reacting for 60s to form a polyamide layer on the surface of the support, forming a cycle, and repeat the cycle twice to obtain a PA film. Take out the PA film and heat treat it at 70°C for 10 minutes to obtain a translucent composite polyamide film with PE / PET composite short fibers as the support layer.

[0080] Example 2

[0081] The composite polyamide membrane was prepared according to the method of Example 1, except that step 3 was replaced by: S3, the support was fixed in the frame, first soaked in an aqueous solution containing 0.05wt% sodium dodecyl sulfate and 3.4wt% m-phenylenediamine for 15min, and then the excess aqueous solution was removed by blowing with an air gun, and then a n-hexane solution containing 0.18wt% trimesoyl chloride and 0.08wt% trimellitic anhydride chloride was poured onto the surface of the modified base membrane, and the excess solution was immediately removed after reacting for 70s to form a polyamide layer on the surface of the support, constituting a cycle, and the cycle was repeated 2 times to obtain the final product PA membrane. The modified base membrane was taken out and heat-treated at 55°C for 20min to obtain a translucent composite polyamide membrane with PE / PET composite short fibers as the support layer.

[0082] Example 3

[0083] The composite polyamide membrane was prepared according to the method of Example 1, except that step 3 was replaced by: S3, the support was fixed in the frame, first soaked in an aqueous solution containing 0.1wt% sodium dodecyl sulfate and 4wt% m-phenylenediamine for 15min, and then the excess aqueous solution was purged with an air gun, and then a n-hexane solution containing 0.2wt% trimesoyl chloride (TMC) and 0.1wt% trimellitic anhydride chloride (TAC) was poured onto the surface of the modified base membrane, and the excess solution was immediately removed after reacting for 50s to form a polyamide layer on the surface of the support, constituting a cycle, and the cycle was repeated 2 times to obtain the final product PA membrane. The modified base membrane was taken out and heat-treated at 75°C for 20min to obtain a translucent composite polyamide membrane with PE / PET composite short fibers as the support layer.

[0084] Example 4

[0085] A composite polyamide membrane was prepared according to the method of Example 1, except that step 1 was replaced by: 500 mg of polyoxyethylene and cationic polyacrylamide were respectively dissolved in 100 mL of deionized water, and ultrasonicated for 10 h with a probe ultrasonicator at a power of 270 W to obtain polyoxyethylene and cationic polyacrylamide solutions; 0.94 g of dry weight of PE / PET composite short fibers was dispersed in 200 ml of deionized water, 2 ml of polyoxyethylene and cationic polyacrylamide solution were added, and a constant temperature magnetic stirrer was used to mix for 10 min at room temperature and a stirring rate of 600 rpm to obtain a mixed solution, and the mixed solution was added to a former to obtain an intermediate by wet forming.

[0086] Example 5

[0087] The composite polyamide membrane was prepared according to the method of Example 1, except that step 2 was replaced by: the intermediate was hot-pressed for 5 minutes by an oil press (pressure 5 MPa) and a vacuum drying oven (temperature 120° C.) to obtain a support having a certain strength and pore size distribution.

[0088] Comparative Example 1

[0089] The composite polyamide membrane was prepared according to the method of Example 1, except that step 3 was replaced by: S3, the modified base membrane was fixed in the frame, first soaked in an aqueous solution containing 3wt% m-phenylenediamine for 15min, and the excess aqueous solution was blown off with an air gun, and then a n-hexane solution containing 0.15wt% trimesoyl chloride and 0.08wt% trimellitic anhydride chloride was poured onto the surface of the modified base membrane, and the excess solution was immediately removed after reacting for 50s to form a polyamide layer on the surface of the support, constituting a cycle, and the cycle was repeated 2 times to obtain the final product PA membrane. The modified base membrane was taken out and heat-treated at 70°C for 10min to obtain a translucent composite polyamide membrane with PE / PET composite short fibers as the support layer.

[0090] Comparative Example 2

[0091] The composite polyamide membrane was prepared according to the method of Example 1, except that step 3 was replaced by: S3, the modified base membrane was fixed in the frame, first soaked in an aqueous solution containing 0.05wt% sodium dodecyl sulfate and 3wt% m-phenylenediamine for 15min, and the excess aqueous solution was removed by blowing with an air gun to obtain a modified base membrane, and then a n-hexane solution containing 0.15wt% trimesoyl chloride was poured onto the surface of the treated modified base membrane, and the excess solution was immediately removed after reacting for 50s to form a polyamide layer on the surface of the support, constituting a cycle, and the cycle was repeated 2 times to obtain the final product PA membrane. The modified base membrane was taken out and heat-treated at 70°C for 10min to obtain a translucent composite polyamide membrane with PE / PET composite short fibers as the support layer.

[0092] Comparative Example 3

[0093] The composite polyamide membrane was prepared according to the method of Example 1, except that step 3 was replaced by: S3, the modified base membrane was fixed in the frame, first soaked in an aqueous solution containing 3wt% m-phenylenediamine for 15min, and the excess aqueous solution was blown away with an air gun to obtain a modified base membrane, and then a n-hexane solution containing 0.15wt% trimesoyl chloride was poured onto the surface of the treated modified base membrane, and the excess solution was immediately removed after reacting for 50s to form a polyamide layer on the surface of the support, constituting a cycle, and the cycle was repeated 2 times to obtain the final product PA membrane. The modified base membrane was taken out and heat-treated at 70°C for 10min to obtain a translucent composite polyamide membrane with PE / PET composite short fibers as the support layer.

[0094] Comparative Example 4: Traditional polysulfone (PSF) support layer

[0095] A composite polyamide membrane was prepared according to the method of Example 1, except that step 1 was replaced by: S1, 80g of polysulfone resin (PSF), 370g of N,N-dimethylformamide (DMF) and 50g of polyethylene glycol 200 (PEG200) were mixed and stirred at 75°C for 6h to prepare a uniformly dispersed casting liquid, the casting liquid was filtered and vacuum degassed, and then evenly coated on a PET non-woven fabric through a scraper. After evaporation at room temperature for 3s, it was immersed in ultrapure water at 10°C to gel and solidify into a film, and then the membrane was completely cured with room temperature water. Finally, the membrane was placed in ultrapure water at 75°C for 3min to obtain a polysulfone support.

[0096] Comparative Example 5: Pure PE support layer

[0097] A composite polyamide membrane was prepared according to the method of Example 1, except that step 1 was replaced by: S1, 500 mg of polyoxyethylene and 500 mg of cationic polyacrylamide were dissolved in 100 mL of deionized water, respectively, and ultrasonicated for 10 h with a probe ultrasonicator at a power of 270 W, and then centrifuged at a speed of 1000 rpm for 1 h to remove the undispersed polyoxyethylene and cationic polyacrylamide to obtain polyoxyethylene and cationic polyacrylamide solutions; 1.88 g of dry weight of polyethylene (PE) chopped fibers were dispersed in 200 mL of deionized water, 2 mL of polyoxyethylene and 2 mL of cationic polyacrylamide solution were added, and a constant temperature magnetic stirrer was used to mix for 10 min at room temperature and a stirring rate of 600 rpm to obtain a mixed solution, and the mixed solution was added to a former to obtain a PE support by wet forming; finally, the PE support was treated with an oxygen plasma system (UVFAB system, CUTE-MPR system), and the plasma exposure time was adjusted to 20 s under the conditions of a fixed plasma power of 20 W and an operating pressure of 0.09 kPa to obtain an intermediate.

[0098] Comparative Example 6

[0099] S1. 1.88 g of dry weight of PE / PET composite short fibers were dispersed in 200 mL of deionized water, and mixed for 10 min at room temperature and at a stirring rate of 600 rpm using a constant temperature magnetic stirrer to obtain a mixed solution, and the mixed solution was added to a former to obtain an intermediate by wet forming;

[0100] S2, hot pressing the intermediate for 5 min by means of an oil press (pressure 5 MPa) and a vacuum drying oven (temperature 100° C.) to obtain a support having a certain strength and pore size distribution;

[0101] S3, fix the support in the frame, soak it in a 3wt% aqueous solution of m-phenylenediamine for 15 minutes, add sodium dodecyl sulfate to the m-phenylenediamine solution, control the concentration of sodium dodecyl sulfate to 0.05wt%, remove the excess aqueous solution with an air gun, add 0.08wt% trimellitic anhydride chloride, and then pour 0.15wt% trimethyl chloride n-hexane solution onto the surface of the treated modified base film, remove the excess solution immediately after reaction for 60s, so as to form a polyamide layer on the surface of the support, forming a cycle, and repeat the cycle twice, and obtain a PA film after heat treatment at 70°C for 10 minutes. After the formation of the polyamide layer, the composite polyamide film is passed through a water bath at room temperature, and then through a subsequent water bath containing 3.5wt% poly(ethylene glycol) diglycidyl ether (PEGDE) at about 100°C, and then coated with 0.1wt% polyacrylamide (PAM) via a contact coater. After coating, heat treatment was performed at 70°C for 10 min to obtain the final translucent composite polyamide film.

[0102] The performance of the translucent composite polyamide films prepared in Example 1 and Comparative Examples 1-6 was tested.

[0103] The water flux and NaCl rejection of the prepared composite polyamide membrane were evaluated using a cross-flow filtration device, in which a circular flat membrane with a diameter of 4 cm (effective membrane area = 14.5 cm 2 )(A). Using NaCl aqueous solution (2000 mg·L -1 ), operating pressure is 15.5 bar (1.55 MPa), temperature is 25.0 ± 5 °C, flow rate is 1 L min -1 (The corresponding cross-flow velocity is 52.7 cm·s -1 ). After 12 hours, when the membrane water flux reaches a stable state, performance data are collected. Water flux (J w ,L·m -2 ·h -1 ) is determined by quantifying the total volume of permeate (ΔV) passing through a predetermined membrane area within a certain time (Δt), such as:

[0104]

[0105] The NaCl retention rate (R, %) was measured by a conductivity meter (Shanghai Leici Co., Ltd., model DDS-307) to determine the NaCl concentration of the feed (Cf) and the permeate (Cp), such as:

[0106]

[0107] Porosity test method:

[0108] The sample was cut into pieces of about 4 cm × 4 cm, placed in an oven to dry for 2 hours, and then weighed and recorded as m1. The sample was then immersed in a n-butanol solution for 6 hours. After being taken out, excess n-butanol on the surface was removed with filter paper, and then weighed and recorded as m2. η is defined as the porosity of the sample, such as:

[0109]

[0110] Where: m1 is the mass of the sample, g; ρ1 is the density of the sample, g·cm -3 ; m0 is the mass of n-butanol, g; ρ0 is the density of n-butanol, g·cm -3 .

[0111] Mechanical properties test methods:

[0112] The test was carried out in accordance with GB / T 1291-2008 Determination of tensile strength of paper and paperboard. Ten specimens with a width of 15 mm and a length of 100 mm were cut and the tensile strength and breaking length of the paper samples were tested using a tensile strength tester. Each paper sample was tested 10 times and the average value was calculated.

[0113] Chemical stability test method:

[0114] The composite membrane was immersed in a tetrahydrofuran (THF) (20%) aqueous solution for 30 min, taken out and washed with deionized water, and the changes in the composite membrane retention rate and water flux before and after immersion were tested and compared to evaluate the chemical stability (resistance to organic solvents) of the composite membrane.

[0115] The test results are shown in Table 1.

[0116] Table 1

[0117]

[0118]

[0119] It can be seen from the results in Table 1 that, compared with the reverse osmosis membranes prepared in Comparative Examples 1 to 6, the reverse osmosis membranes prepared in Examples 1 to 5 of the present invention have excellent water flux and higher retention rate.

[0120] Specifically:

[0121] Combining Example 1 of the present invention with Comparative Example 1, it can be seen that the salt rejection rate of the reverse osmosis membrane obtained by lacking sodium dodecyl sulfate in the aqueous phase system is significantly reduced; Combining Example 1 of the present invention with Comparative Example 2, it can be seen that the salt rejection rate of the reverse osmosis membrane obtained by lacking trimellitic anhydride chloride in the oil phase system is also significantly reduced; Combining Example 1 of the present invention with Comparative Example 3, it can be seen that the reverse osmosis membrane obtained by lacking both sodium dodecyl sulfate and trimellitic anhydride chloride has a more obvious reduction in salt rejection rate. This shows that: in the system of the present invention, the simultaneous use of sodium dodecyl sulfate and trimellitic anhydride chloride can cooperate to achieve a better salt rejection rate effect.

[0122] Combining Example 1 of the present invention with Comparative Examples 4-5, it can be seen that the type of support layer is very important. The present invention can obtain a reverse osmosis membrane with better rejection rate and better resistance to organic solvents by selecting a support layer constructed of PE / PET composite short fibers. However, the performance of the reverse osmosis membrane obtained by using the traditional PSF support layer or the simple PE short fiber support layer involved in Comparative Documents 4 and 5 is not good.

[0123] Combining Example 1 of the present invention and Comparative Example 6, it can be seen that polyacrylamide is not added to S1, but polyacrylamide is used for coating at the end. Comparison of the two methods shows that the method of the present invention can obtain excellent interception rate and organic solvent resistance effect.

[0124] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composite polyamide membrane, characterized in that: The composite polyamide membrane comprises a support layer and a polyamide layer. The support layer is prepared by using PE / PET composite short fibers through a wet nonwoven technology, and the polyamide layer contains a reaction product of metaphenylenediamine and trimesoyl chloride.

2. The composite polyamide membrane according to claim 1, characterized in that The support is made of PE / PET composite short fibers.

3. A method for preparing the composite polyamide membrane according to claim 1, characterized in that: The method comprises the following steps: S1, dispersing PE / PET composite short fibers, polyethylene oxide, and cationic polyacrylamide in deionized water, stirring and mixing to obtain a uniform mixed solution, and forming the mixed solution on a former to obtain an intermediate; S2, hot pressing and drying the intermediate to obtain a support; S3, sequentially treating the support with a m-phenylenediamine solution containing sodium dodecyl sulfate and a trimesoyl chloride solution containing trimellitic anhydride chloride to form a polyamide layer on the surface of the support to obtain a composite polyamide membrane.

4. The preparation method according to claim 3, characterized in that: In step S1, the mass ratio of PE / PET composite staple fibers, polyethylene oxide, and cationic polyacrylamide is (100-500):1:(0.5-1.5).

5. The preparation method according to claim 3, in step S1, the stirring and mixing conditions at least include: The temperature is 20-30°C, the stirring rate is 500-700rpm, and the time is 10-20min.

6. The preparation method according to claim 3, characterized in that: In step S2, the conditions for hot pressing drying are: pressure of 5 MPa, hot pressing temperature of 100° C., and hot pressing time of 5-10 min.

7. The preparation method according to claim 3, characterized in that: In step S3, the solvent used in the m-phenylenediamine solution is deionized water; the solvent used in the trimesoyl chloride solution is n-hexane; the concentration of m-phenylenediamine in the m-phenylenediamine solution is 3-4wt%, and the concentration of sodium dodecyl sulfate is 0.05-0.1wt%; the concentration of trimesoyl chloride in the trimesoyl chloride solution is 0.15-0.2wt%; and the concentration of trimellitic anhydride chloride is 0.08-0.1wt%.

8. The preparation method according to claim 3, characterized in that In step S3, the support is treated with a m-phenylenediamine solution containing sodium dodecyl sulfate and a trimesoyl chloride solution containing trimellitic anhydride chloride in sequence to form a polyamide layer on the surface of the support, which constitutes a cycle. The cycle is repeated 0-2 times, and finally a composite polyamide film is obtained by heat treatment.

9. The preparation method according to any one of claims 3 to 8, characterized in that: The heat treatment conditions at least include: a temperature of 65-75° C. and a time of 10-20 min.

10. Use of the composite polyamide membrane according to any one of claims 1 to 2, or the composite polyamide membrane prepared by the method according to any one of claims 3 to 8 in the field of reverse osmosis.